Analisis Perancangan Optimalisasi Database Akses Pemakaian Ruang Kelas di Perguruan Tinggi Berbasis RFID - Filda Angellia (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
A manual classroom usage scheduling system that is currently running in several universities has many shortcomings, including time efficiency including waiting times for classrooms opening and readjustments if there is a conflicting classroom usage schedule (together). This problem can only be resolved if there is a network database utilization process, one of which is by using RFID (Radio Frequency Identification) based technology that can be utilized as a network database based tool for optimizing access to use of classrooms and used as an identification card in classroom access systems. This research was conducted with the intention to reduce the flow of manual procedures and reduce waiting times when going to use the classroom and this system is also intended to avoid concurrent schedules (conflicting schedules) in the use of classrooms. The method in this study can continue to develop with qualitative methods based on experiments, where the authors make a system that uses a database system to manage the recording of classroom usage so that all users of classroom access can be detected from time to time. The system that was designed on the basis of RFID is expected to continue to develop into a reliable prototype.